An Investigation on The Use of Social Strategies in Online EFL Learning - Ismiatun, Febti; Suhartoyo, Eko (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
Abstract: This study aims to investigate the use of social strategies in English as A Foreign Language (EFL) learning. This was inspired by the learning condition that has been changing from face-to-face atmosphere to the online-based due to the Covid-19 pandemic. This changing situation requires teachers and students to be more aware of applying suitable strategies in online learning mode, especially social strategies. Using the descriptive qualitative approach, this study was conducted on the fourth semester EFL students in a private university. To elicit the required data, set of online questionnaires was disseminated to 50 participants to obtain information on social strategies use in online EFL learning. The result of the descriptive analysis showed that average students exhibited a high frequency of using social strategies in their learning processes. In asynchronous learning, students preferred doing ‘collaboration and discussion’ to assess their completed task. The strategies of ‘using tools to improve interaction and communication as well as asking for clarification’ were more influential in synchronous learning in which technology effected the use of social strategies in the online class participation. Therefore, it becomes crystal clear that social strategies are deemed effective to aid online EFL learning. Further suggestions regarding the use of social strategies are also accessible at the end of this article.